1991
DOI: 10.1038/ki.1991.155
|View full text |Cite
|
Sign up to set email alerts
|

Significance of anti-phospholipid antibodies in patients with lupus nephritis

Abstract: Anti-phospholipid antibodies (APA) as markers or mediators of thrombosis in lupus could be of pathogenetic significance in nephritis, since glomerular capillary thrombi are an indicator of subsequent renal dysfunction. Isotype specific APA antibodies were measured, using cardiolipin as the antigen, in 76 patients with lupus nephritis. Twenty-nine percent of the patients had elevated IgG APA. Overall, 43% of patients showed raised levels of at least one isotype. In general, APA had specificity for anionic phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
36
1
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 16 publications
9
36
1
3
Order By: Relevance
“…The prevalence of aPL antibody was similar to that reported in many other studies of patients with SLE (19), it was also apparently similar to that reported from previous studies of patients with lupus nephritis (7,8,12,20). Forty-one percent of our patients developed vascular thrombosis, similar to that reported recently for a lupus nephritis series (21).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The prevalence of aPL antibody was similar to that reported in many other studies of patients with SLE (19), it was also apparently similar to that reported from previous studies of patients with lupus nephritis (7,8,12,20). Forty-one percent of our patients developed vascular thrombosis, similar to that reported recently for a lupus nephritis series (21).…”
Section: Discussionsupporting
confidence: 79%
“…antibodies on the outcomes of lupus nephritis are conflicting, mainly because they are based on studies with short follow-up periods (8)(9)(10)(11)(12).…”
Section: Antiphospholipid Syndrome (Aps) Is a Disorder Characterized mentioning
confidence: 99%
“…34 35 Loizou et al found that raised levels of aCL were associated with LN but were unable to show an association with anti-β 2 -glycoprotein I and did not look for the presence of LA. Moreover, they found that the presence of aCL in conjunction with raised levels of anti-dsDNA and anti-C1q antibodies is highly specific for LN.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors investigated the role of the antiphospholipid antibodies in systemic lupus erythematosus (SLE) patients with renal involvement [22][23][24][25]. Farrugia et al [22] compared LACnegative SLE patients with renal dysfunction to SLE patients with renal impairment and detectable LAC.…”
Section: Discussionmentioning
confidence: 99%